Recent changes in ENSO’s impacts on the summertime circumglobal teleconnection and mid-latitude extremes - Shankai Tang; Shaobo Qiao; Bin Wang; Fei Liu; Xian Zhu; Taichen Feng; Guolin Feng; Wenjie Dong (Nature Communications)
Abstract The boreal summer circumglobal teleconnection (CGT) provides a primary predictability source for mid-latitude Northern Hemisphere climate anomalies and extreme events. Here, we show that the CGT’s circulation structure has been displaced westward by half a wavelength since the late 1970s, more severely impacting heatwaves and droughts over East Europe, East Asia, and southwestern North America. We present empirical and modelling evidence of the essential role of El Niño-Southern Oscillation (ENSO) in shaping this change. Before the late 1970s, ENSO indirectly promoted CGT by modulating the Indian summer monsoon rainfall (ISMR). Since 1980s, the ENSO–ISMR link has weakened, but the westward-displaced ENSO forcing has been able to directly trigger a Rossby wave response at the exit of the East Asian westerly jet, resulting in a shift of the previous CGT’s North Pacific and downstream centers westward along the westerly jet waveguide. State-of-the-art climate models with prescribed anthropogenic forcing cannot simulate these changes, suggesting that they are driven by natural variability. This work highlights the importance of studying the impacts of changing ENSO to improve seasonal prediction of mid-latitude extreme events.